Mycobacterial Brain Tuberculomas due to Bacille Calmette-Guérin Intravesical Chemotherapy for Bladder Cancer: A Case Report and Literature Review - Vitaly Golub; Prashant Malhotra; Shital Patel (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacille Calmette-Guérin (BCG) immunotherapy is widely used for the treatment of superficial bladder cancer. The authors believe that the present report is one of the first to document cerebral BCG tuberculoma in a 73-year-old immunocompetent man, three years after intra-vesical BCG immunotherapy. His workup revealed no identifiable extracranial source. He responded well to treatment with rifampin, ethambutol and moxifloxacin.